Situation Report: Bulgaria, 18 April 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Bulgarian Military, Macedonia, and the "Lyudmila Effect" / by Patrick Moore New Committee on Labor and Social Matters / by Rada Nikolaev Women's Liberation: Some Views Some Problems of the Machine-Building Industry Law on Plebiscites Receives "Parliamentary Blessing" / by Rada Nikolaev